TRANSWOMAN MOTHERHOOD: ANALYZING FILM DIE BEAUTIFUL WITHIN BUTLER’S GENDER PERFORMATIVITY THEORY - Flores, June Louie A.; Elfira, Mina (UI Scholars Hub, 2026)
This study explores the representation and construction of gender identity and motherhood of transgender women within the Philippine society, focusing on Jun R. Lana’s 2016 film, Die Beautiful. Recognizing the increasing visibility of the queer community in media and social discourse, the research aims to analyze how the film reflects and challenges the binary construction of gender and societal gender norms using the theory of gender performativity by Judith Butler from her book Gender Trouble. Employing a qualitative content analysis approach, specifically the conventional method, selected scenes were examined to identify instances of gender performance and explore how social expectations influence gender identity and expression. The findings suggest that Die Beautiful strongly exemplifies gender as performative, highlighting that identity is constructed through repeated actions and social influences rather than innate traits. The film’s nuanced portrayal of transgender individuals’ struggles and self-expression contributes to a small theoretical framework that affirms gender performativity as a means to challenge binary notions and promote inclusivity within the Philippine culture.